2017
DOI: 10.4236/me.2017.812103
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Ergonomics on Employee Productivity: A Case Study of the Butchering and Trimming Line of Pioneer Food Cannery in Ghana

Abstract: This study sought to investigate the effect of ergonomics on the employee productivity focusing on the Butchering and Trimming Line of Pioneer Food Cannery Limited (PFC) in Ghana. Research questionnaires were developed and distributed to a sample of 134 workers consisting of workers in charge of butchering, trimming as well as supervisors. It was evident from the findings that all the indicators explaining work ergonomics from the perspective of the employees of PFC were satisfactory despite the few respondent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…This might in turn affect the performance levels of the employees and act as a loss for the organisation as a whole. Following from the previously documented literature, this research takes up the identified ergonomic elements to study their impact on the performance levels of employees [15].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…This might in turn affect the performance levels of the employees and act as a loss for the organisation as a whole. Following from the previously documented literature, this research takes up the identified ergonomic elements to study their impact on the performance levels of employees [15].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…further, Harris (1994) has been indicated that his definition of individual work productivity includes effectiveness(producing the right products or services), efficiency(prudent utilization of resources), and quality(meeting technical and customer specifications). Pickson et al (2017) used job satisfaction for investigating the effect of ergonomics on employee productivity. So, when measuring work productivity of computer operators' researcher has been taken some assorted dimensions through the above literature regarding computer operators' work productivity.…”
Section: Computer Operators' Work Productivitymentioning
confidence: 99%
“…From this, it may be concluded that the impact of indoor room temperature is more on the office worker's performance than the effect of illumination. (Pickson et al, 2017) Investigating Ergonomic approach in the manufacturing production system can reduce defects and improve quality in the production process.…”
Section: Organizational Ergonomic Factorsmentioning
confidence: 99%
“…Implementation of the study of ergonomic solutions can provide employees a better and comfortable working environment and also increase productivity. The temperature and noise are the most important vital factors that affect the performance of workers in casting industries [4,5]. Generally speaking ergonomics have many advantages in industries such as improves productivity and quality, employee engagement, increase saving.…”
Section: Ergonomicmentioning
confidence: 99%